2007
DOI: 10.1017/s1074070800022793
|View full text |Cite
|
Sign up to set email alerts
|

Trade Creation and Trade Diversion in the North American Free Trade Agreement: The Case of the Agricultural Sector

Abstract: This paper examines the effect of the U.S.-Mexico trade agreement under the North American Free Trade Agreement (NAFTA). The results suggest that U.S. agricultural imports from Mexico have been responsive to tariff rate reductions applied to Mexican products. A one percentage point decrease in tariff rates is associated with an increase in U.S. agricultural imports from Mexico by 5.31% in the first 6 years of NAFTA and by 2.62% in the last 6 years of NAFTA. U.S. imports from Mexico have also been attributable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…They also found that RTAs did not always cause trade diversion from nonmember countries. Susanto, Rosson, and Adcock (2007) examined the impacts of the U.S.–Mexico bilateral agreement under NAFTA on agricultural trade using tariff data. Sarker and Jayasinghe (2007) analyzed the trade effects of the EU through binary variables using a dataset covering six agricultural commodities.…”
Section: Introductionmentioning
confidence: 99%
“…They also found that RTAs did not always cause trade diversion from nonmember countries. Susanto, Rosson, and Adcock (2007) examined the impacts of the U.S.–Mexico bilateral agreement under NAFTA on agricultural trade using tariff data. Sarker and Jayasinghe (2007) analyzed the trade effects of the EU through binary variables using a dataset covering six agricultural commodities.…”
Section: Introductionmentioning
confidence: 99%
“…Grant and Lambert (2008) tested the hypothesis that RTA effects are greater for agricultural trade than for nonagricultural trade. Susanto et al (2007) investigated the impacts of the Unites States–Mexico bilateral agreement under NAFTA on aggregate agricultural trade using tariff data 5 . Despite the voluminous body of work on agricultural trade determinants, it is fair to say that the literature on the extensive margin of trade in agriculture is relatively scant.…”
Section: Introductionmentioning
confidence: 99%
“…Samba and Yan (2009) found similar results for selected East Asian Countries, pointing out that international trade leads to financial development in most of the countries in the sample. Susanto et al (2011) found the positive effect of financial development on bilateral trade flows and that the effect is more prominent in the manufacturing sector, with relatively large economies of scale. Furthermore, according to the results of their research, an export from developing countries is more affected by financial development than an export from developed countries.…”
Section: Brief Literature Overviewmentioning
confidence: 94%